Performance and carcass characteristics of cull beef cows implanted with growth promotants and fed a high concentrate ration - C.D. Cranwell; D.D. Simms; J.R. Brethour; John A. Unruh (Kansas Agricultural Experiment Station Research Reports, 1992)
Open, cull beef cows fed a high concentrate ration for 28 or 56 days and implanted with Finaplix-H®, Synovex-H®, or both had improved gain and feed efficiency compared to controls (nonimplanted cows). Changes in ultrasound-measured backfat (12th rib) of implanted cows and controls were similar in both feeding periods. Marbling, fat color, and tenderness, as measured by Warner-Bratzler shear force, were not improved by feeding cows for 56 days compared to 28 days. However, lean color, dressing percent, and ribeye area were improved by feeding for 56 days. Numerical yield grade was lower (P<.05) in 28-day fed cows. Implanting with Synovex-H or Finaplix-H resulted in leaner carcasses with lower yield grades compared to controls. Ribeye area was increased by using Synovex-H compared to controls and Finaplix- H. These data indicate that the benefits in gain, feed efficiency, and carcass traits from implanting cull cows can be obtained by using either Synovex-H or Finaplix-H alone.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Cull cow; Implant; Gain; Efficiency; Carcass